0246 The impact of high-school completion - a multi-state model for work participation and health-related absence in young men. (21st August 2017) - Hoff, Rune; Mehlum, Ingrid; Corbett, Karina; Mohn, Ferdinand; Hanvold, Therese; Kristensen, Petter; Gran, Jon Michael
Abstract : Background: Completing high school is associated with higher work participation and lower health-related absence. Few studies consider the dynamics of such outcomes over time. We assessed how high school completion affected work participation and health-related absence in young men over a 14.5 year follow-up period, using multi-state models. Methods: Baseline covariates and follow-up data on five states: work, education, unemployment, sick leave and disability, were obtained from national registries for all males born in Norway between 1971 and 1976 (n=184 951). The impact of high school completion (before age 21) on transitions between states from age 21 to 35 was analysed using Cox proportional hazards models. Population average effects were assessed by analysing data weighted by individuals' inverse probability of high school completion. Long-term impacts are illustrated by probabilities for all states during follow-up. Results: For Norwegian men, high school completion was strongly associated with higher work participation and lower health-related absence. When adjusting for baseline covariates, associations were reduced although still substantial. Right after start of follow-up, the crude probability for unemployment was 20.9 percentage points (pp) lower for completers compared to non-completers, and 2.3 pp lower for sick leave. In the weighted analysis, the corresponding differences were 16.5 and 1.5 pp. Near the end of follow-up, the crude differences were 6.9 pp for unemployment and 3.8 pp for sick leave. Corresponding numbers were 3.9 and 1.8 pp in the weighted analysis. Conclusion: The results suggest that completing high school increases long-term work-participation and lowers health-related absence for young men.